2005
DOI: 10.1136/bmj.38398.500764.8f
|View full text |Cite
|
Sign up to set email alerts
|

Improving clinical practice using clinical decision support systems: a systematic review of trials to identify features critical to success

Abstract: Objective To identify features of clinical decision support systems critical for improving clinical practice. Design Systematic review of randomised controlled trials. Data sources Literature searches via Medline, CINAHL, and the Cochrane Controlled Trials Register up to 2003; and searches of reference lists of included studies and relevant reviews. Study selection Studies had to evaluate the ability of decision support systems to improve clinical practice. Data extraction Studies were assessed for statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,683
6
28

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,182 publications
(1,798 citation statements)
references
References 50 publications
45
1,683
6
28
Order By: Relevance
“…shown that CDSS that provide information to clinicians at the point of decision making are more likely to be associated with positive outcomes [46]. in turn lead to consequences of the technology which were unintended when it was introduced, or produce 'workarounds' to ensure that the technology 'fits' with existing work processes.…”
Section: Discussionmentioning
confidence: 99%
“…shown that CDSS that provide information to clinicians at the point of decision making are more likely to be associated with positive outcomes [46]. in turn lead to consequences of the technology which were unintended when it was introduced, or produce 'workarounds' to ensure that the technology 'fits' with existing work processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies have focused on the impact of features at the computer interface level and the work process level [23]. [26].…”
Section: Influences On the Use Of Cdssmentioning
confidence: 99%
“…The work of many authors supports the evidence that decision support systems can be extremely effective in improving the quality and safety of healthcare (e.g. [3,[7][8][9][10]). The most famous expert systems were built as diagnosis assistants and therapy advisors in different medical areas (MYCIN [11], ONCOCIN [12], etc.)…”
Section: Introductionmentioning
confidence: 55%